SISTEM MONITORING DAN PEMBERIAN PAKAN IKAN HIAS OTOMATIS BERBASIS WEB - Fadillah, Arkan; Purwanto, Purwanto; Budiyanto, Utomo; Amini, Safrina (Universitas Budi Luhur, 2023)
One important factor to increase the percentage of success for ornamental fish enthusiasts or hobbyists in raising ornamental fish is to pay attention to seed quality, feed quality, and water treatment systems. is that the feeding of ornamental fish is not timely and even forgotten because of the busyness of the ornamental fish hobbyist and monitoring of water temperature is not carried out routinely and in real time. To overcome problems in feeding and monitoring water temperature, an automatic ornamental fish feeding system and internet of things-based temperature monitoring was designed so that it can help the work of ornamental fish enthusiasts or hobbyists. The research objective is to create an automatic ornamental fish monitoring and feeding system with a DS18b20 temperature sensor , ESP32Cam and web-based NodeMCU ESP8266 microcontroller. Based on the test results of this automatic feeding system, the system has succeeded in providing ornamental fish feed on schedule and sending photos from ornamental fish habitat to the web server with a delay of 1 to 3 seconds, monitoring running temperature properly with normal temperatures up to 270C so that the buzzer will activate if the water temperature is above 270C. The web-based monitoring system works well by displaying sensor readings and daily reports of sensor readings.